Do women with PCOS have a unique predisposition to obesity? - Hoeger, Kathleen M.; Oberfield, Sharon E. (Fertility and sterility, 2012)
Women with PCOS are often obese and there is debate in the literature regarding whether women are obese because of their PCOS status or if those who become obese are more predisposed to PCOS. There is support for a predisposition to obesity by some data indicating impaired metabolism in PCOS women compared to weight matched controls but this data is limited. Contrary data also exist that adiposity rates do not vary between women with PCOS and those without, and that differences in obesity rates between countries are more likely due to environmental and lifestyle factors. Until further data are available, lifestyle recommendations for weight reduction in women with PCOS should be similar to those for women without PCOS.